Guidelines for Design of Transversely Stiffened Thin Walled Steel Plates - Bedair, Osama (Recent Patents on Engineering, 2016)
Background: Stiffened plates are commonly used in many engineering applications. Engineers in practice encounter many challenges in the analysis and design of stiffened plates due to the modelling complexities and many parameters involved. Little guidelines are available in industrial codes of practice for the design of stiffened plates. This article reviews recent developments and patents related to analysis and design of thin walled stiffened steel plates. Various numerical procedures used for static and dynamic analysis are reviewed. Engineering Patents describing various cost effective fabrication procedures are briefly discussed. Objectives: The paper illustrates the behaviour of stiffened steel supports under static and dynamic loadings. Design guidelines are presented that can be utilized in practice. Method: The potential energy is expressed in terms generalized functions that describe the displacement profile. The resulting non-linear functions are minimized with respect displacement coefficients. Results: Numerical results are presented to highlight the essential parameters that need to be considered in the design of transversely stiffened panels. Influence of the web and flange geometrical sizes on the stability of stiffened supports are also illustrated. Design curves are provided that can be utilized in the industry to optimize the design of stiffened steel supports. Conclusion: It is shown that the number of longitudinal stiffening configuration largely influence the magnitude of the natural frequency and the buckling coefficients. The results are very useful and can be utilized in the industry very effectively for the steel supports.
Keywords: Finite element